Cross-Domain Effects of Ethical Leadership on Employee Family and Life Satisfaction: the Moderating Role of Family-Supportive Supervisor Behaviors - Zhang, Shuxia (Journal of business ethics, 2018)
Drawing on the work–family enrichment theory, the present study investigates the cross-domain effects of ethical leadership on employees’ family and life satisfaction. Moreover, it focuses on the mediating role of work–family enrichment (WFE) and the moderated mediation process of family-supportive supervisor behaviors (FSSB) underlying the relationship between ethical leadership and employees’ family and life satisfaction. Using a sample of 371 employees and their immediate supervisors in China, we found that WFE mediated the relationship between ethical leadership and employee-rated and supervisor-rated family and life satisfaction. Moreover, FSSB positively moderated the relationship between ethical leadership and WFE, such that the relationship was strengthened when FSSB were higher. Furthermore, the mediations of WFE between ethical leadership and employee-rated and supervisor-rated family and life satisfaction were also positively moderated by FSSB, such that the indirect effects were stronger when FSSB were higher. The theoretical and managerial implications of our findings are further discussed.